PINK1 and Parkin to control mitochondria remodeling - Koh, Hyongjong (Korean Association of Anatomists, 2010)
Parkinson's disease (PD), one of the most common neurodegenerative diseases, is characterized by movement disorders and a loss of dopaminergic (DA) neurons. PD mainly occurs sporadically, but may also result from genetic mutations in several PD-linked genes. Recently, genetic studies with Drosophila mutants, parkin and PINK1, two common PD-associated genes, demonstrated that Parkin acts downstream of PINK1 in maintaining mitochondrial function and integrity. Further studies revealed that PINK1 translocates Parkin to mitochondria and regulates critical mitochondrial remodeling processes. These findings, which suggest that mitochondrial dysfunction is a prominent cause of PD pathogenesis, provide valuable insights which may aid in the development of effective treatments for PD.